2021
DOI: 10.17762/turcomat.v12i6.2484
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Evaluation of Impact of Education Quality on Economic Growth in Azerbaijan

Abstract: The article is dedicated to study of the impact of the quality of education on the economic growth in Azerbaijan. The quality index of education has been selected for two levels: a) up to higher education; b) higher school and post higher school. The indicator of average score (if available) that an applicant obtained in the current year on the country in student admission to the higher schools as a quality index of education in the country at the pre-higher education is offered as an alternative to the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…After analyzing all provided correlational results, it can be concluded that the SEC proved the exams responded to criterion, content, and construct validity for years (Drummond & Gabrscek, 2012). As stated by Hajiyev et al, (2021):…”
Section: Discussionmentioning
confidence: 80%
“…After analyzing all provided correlational results, it can be concluded that the SEC proved the exams responded to criterion, content, and construct validity for years (Drummond & Gabrscek, 2012). As stated by Hajiyev et al, (2021):…”
Section: Discussionmentioning
confidence: 80%